JQuery : a beginner's guide - Pollock, John (New York : McGraw-Hill Education, 2014)
"Learn the fundamentals of jQuery programming in no time. jQuery: A Beginner's Guide starts with the basics--from including the library in an HTML document to element selection, event handling, and CSS style manipulation. Next, it's on to JavaScript and the DOM, animation and effects, the Event object, and form validation. The book then delves into AJAX and plugins and covers more advanced techniques such as debugging and unit testing. Get started with jQuery right away using this fast-paced tutorial!"--
Machine generated contents note: Ch1: Getting Started with jQuery -- Ch2: Selecting Elements in the Document -- Ch3: The Document Object Model -- Ch4: Event Handling -- Ch5: The Event Object -- Ch6: Working with Styles -- Ch7: Animations and Effects -- Ch8: Working with the DOM -- Ch9: Working with AJAX -- Ch10: Using Plugins -- Ch11: How to Create Plugins -- Ch12: Advanced Techniques.
Includes bibliographical references and index.
Keywords: JavaScript (Computer program language); Query languages (Computer science); COMPUTERS / Programming Languages / JavaScript